Umbilical Mass with Cyclical Pain: Surgical Management - Hung, Kay; Knowlton, Lisa Marie; Cha, Peter; Howitt, Brooke; Management, Aussama K Nassar. Umbilical Mass with Cyclical Pain: Surgical (Archives of Clinical and Medical Case Reports, 2021)
Abstract not available in the source database.